2020
DOI: 10.1111/tbj.13737
|View full text |Cite
|
Sign up to set email alerts
|

Sentinel lymph node positivity in patients undergoing mastectomies for ductal carcinoma in situ (DCIS)

Abstract: Breast J. 2020;26:931-936. wileyonlinelibrary.com/journal/tbj | 931 Abstract Current guidelines recommend sentinel lymph node biopsy (SLNB) for patients undergoing mastectomy for a preoperative diagnosis of ductal carcinoma in situ (DCIS). We examined the factors associated with sentinel lymph node positivity for patients undergoing mastectomy for a diagnosis of DCIS on preoperative core biopsy (PCB). The Institutional Breast Cancer Database was queried for patients with PCB demonstrating pure DCIS followed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 27 publications
5
13
0
Order By: Relevance
“…100% of sentinel lymph nodes were found by using the lymphoscintigraphy and dual technique, and a 10% (n = 4) positivity of the sentinel node. [16,17]. Van Roozendaal et al in the Netherlands also reported 9.3% sentinel node positivity, with 3.8% positivity with isolated cells, 3% micrometastasis, and 2.5% macrometastasis, results similar to those of our study [10].…”
Section: Discussionsupporting
confidence: 91%
“…100% of sentinel lymph nodes were found by using the lymphoscintigraphy and dual technique, and a 10% (n = 4) positivity of the sentinel node. [16,17]. Van Roozendaal et al in the Netherlands also reported 9.3% sentinel node positivity, with 3.8% positivity with isolated cells, 3% micrometastasis, and 2.5% macrometastasis, results similar to those of our study [10].…”
Section: Discussionsupporting
confidence: 91%
“…In the current study, we enrolled 682 pre-OP DCIS patients and compared ALN metastasis pattern with another cohort of 2268 pre-OP diagnosed invasive cancer. We found 34.2% of these pre-OP DCIS patients upgraded to DCIS-IC in nal pathology, and this upgrade rate was consistent with literate reported range (3.5-56%) [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. The risk of ALN metastasis rate varied widely depends on the pre-operative pathology, and in our current study, the ALN metastasis rate is 7.6% in pre-OP DCIS patients, and up to 39% in pre-OP invasive cancer group (Table 2).…”
Section: Discussionsupporting
confidence: 88%
“…In theory, ductal carcinoma in situ (DCIS) does not metastasize to adjacent lymph nodes, and axillary lymph node evaluation or surgery had limited role. DCIS as determined by pathologic analysis of biopsy specimens, however, does not preclude invasive disease in excised specimens, and up to 50% (range, 3.5-56%) of core needle biopsy (CNB) or vacuum-assisted core biopsy (VACB) diagnosed DCIS would upgrade to have an invasive component (IC) [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. Indication and adequacy of application of SLNB in lymph node evaluation of patients with pre-operative (pre-OP) DCIS diagnosed by biopsy remained a debated issue as SLNB remains an invasive procedure and not morbidity free [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 2 , 30 The number of surgeons who have discontinued the use of SLNB during breast conservative surgery, reserving this technique only for mastectomy cases, is increasing. 28 , 31 …”
Section: Discussionmentioning
confidence: 99%